2004
DOI: 10.2188/jea.14.204
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Class and Exposure to Job Stressors among Employed Men and Women in Japan

Abstract: parts producer. Only full-time employees were invited to participate in the study. At four study sites, all full-time employees were invited. At three other sites, full-time employees who participated in health checkups within a certain period were invited. At one site, full-time employed men who had participated in health checkups were invited. At another site, all supervisors and managers were invited. A questionnaire was distributed by mail with a letter of invitation explaining the objectives and procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 22 publications
(51 reference statements)
4
53
6
Order By: Relevance
“…Male managers showed a low prevalence OR of being in the high occupational stress group in JDC stress (high demands, low decision latitude), which coincides with the results by Kawakami et al 24) . However, production workers/ laborers showed a lower prevalence OR of being in the high occupational stress group, compared to managers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Male managers showed a low prevalence OR of being in the high occupational stress group in JDC stress (high demands, low decision latitude), which coincides with the results by Kawakami et al 24) . However, production workers/ laborers showed a lower prevalence OR of being in the high occupational stress group, compared to managers.…”
Section: Discussionsupporting
confidence: 90%
“…Research on occupational class and exposure to job stressors is limited in Japan. As a result of a study based on JDC, Kawakami et al have found connections between nine occupational categories and job stressors among Japanese employed men and women, also reporting that low-grade occupations such as laborers and machine operators are highly exposed to low job control and high job strain 24) . Sekine et al have reported that job stress differs according to employment grade, high grades being characterized by high job control and high job demands 19) .…”
Section: Introductionmentioning
confidence: 99%
“…The present study was conducted using the data obtained as a baseline survey of the Japan Work Stress and Health Cohort Study (JSTRESS Study) (reported in detail elsewhere 41,42) ). A questionnaire was distributed to 29,471 workers at nine companies and factories from April 1996 to May 1998; 25,104 workers replied (average response rate, 85.2%).…”
Section: Subjectsmentioning
confidence: 99%
“…This could be because job strain was significantly correlated with occupations in this cohort group 23) . On the contrary, there is an argument that the job strain model might be too simple to show the differences among occupations 24) , even though the categories of occupations have not been established among health researchers.…”
Section: Discussionmentioning
confidence: 81%
“…In model 3, we adjusted for age, education, marital status and job strain. To avoid over-adjustment [21][22][23][24] , in model 3, we adjusted for not occupations but job strain. Odds ratios were converted to adjusted relative risk (ARR) by means of the formulas which Zhang et al indicated 25) .…”
Section: Discussionmentioning
confidence: 99%